2008
DOI: 10.1002/jmv.21290
|View full text |Cite
|
Sign up to set email alerts
|

A wide spectrum of dengue IgM and PCR positivity post‐onset of illness found in a large dengue 3 outbreak in Pakistan

Abstract: During a large outbreak of dengue serotype 3 in Pakistan in 2006, multiple serum samples were routinely collected for laboratory testing. Two hundred ninety-seven samples were collected between August and November 2006. Serological testing for dengue IgM was performed in Pakistan and polymerase chain reaction (PCR) testing for dengue RNA detection and serotyping were performed in Hong Kong. Dengue-specific IgM was detectable as early as 1 day, and dengue RNA remained detectable for up to 14 days, post-onset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Considering the dynamics of the immune response, typically viremia diminishes around the time the patient has detectable IgM antibodies. Additionally, a study in Pakistan found that significant clinical illness was more likely to be associated with being positive for IgM and negative for RNA (Tang et al 2008). Another possible reason for the low numbers of PCRpositive specimens could be related to specimen storage and the integrity of the samples.…”
Section: Dengue In Houston Texasmentioning
confidence: 99%
“…Considering the dynamics of the immune response, typically viremia diminishes around the time the patient has detectable IgM antibodies. Additionally, a study in Pakistan found that significant clinical illness was more likely to be associated with being positive for IgM and negative for RNA (Tang et al 2008). Another possible reason for the low numbers of PCRpositive specimens could be related to specimen storage and the integrity of the samples.…”
Section: Dengue In Houston Texasmentioning
confidence: 99%
“…10,11,18 It is speculated that dengue virus may have been endemic in Pakistan, but due to lack of any effective surveillance and diagnostic measures, no outbreaks were reported until 1994, when introduction of DENV-1 serotype caused a major outbreak in southern Pakistan with high morbidity and mortality rates. 23 After a gap of almost 10 years, dengue outbreaks ensued again in 2005/2006 claiming many deaths, 24 with circulating serotypes of DENV-2 and the new DENV-3 (New Delhi genotype). 25,26 Since 2006, the disease extended its range from southern to northern Pakistan, resulting in outbreaks that have affected thousands of people, causing hundreds of mortalities over the course of past 7 years or so.…”
Section: Introductionmentioning
confidence: 99%
“…Dengue was not endemic in the country at that time but since then cases that are detected per year are on the rise. [3,4]. In 2007, dengue infection mainly hit Karachi, Mirpurkhas, Lahore, Hyderabad, Haripur, Islamabad and Rawalpindi with 2700 cases [5,6].…”
Section: Letter To Editormentioning
confidence: 99%